Comparison of tourist traffic by railway and automobile transport and methodical approach to determining the costs of such transportations - Barash, Yurii; Hnennyi, Oleh; Martseniuk, Larysa; Charkina, Tetiana (Technology audit and production reserves, 2017)
To increase the competitiveness of railway transport the authors propose to develop of railway tourism in Ukraine. The article aims to systematize the advantages and disadvantages of railway and automobile tourism and develop efficient areas of their use in this context. Moreover, the authors set a goal to develop a methodical approach to determine the costs of the company that will organize transportations on the specific tourist route. Studies have shown that tourist traffic by railway transport has high potential, provided that it will use modern comfortable rolling stock and have in its structure not only the cars for tourist transportation, but also dining car, casino car, disco car (during the day game car for kids) and others. The above mentioned set of cars should be recommended for cruise travel with a period from 8 to 28 days, for shorter journeys the tourist train may not include casino car, disco car (during the day game car for kids) and others. The final choice of tourist traffic should be justified by economic calculations using the method proposed by this article. The approach is based on accounting all complex of costs associated with the technological process of tourism services. It includes the costs for the process of transportation itself, delivery of additional services of infrastructure and rolling stock owners, pay for transfer transportations, services of hotels, restaurants, cafes, travel agencies, advertising organizations and own costs of travel company. It makes possible to determine the costs of travel package more accurately, taking into account the demand for this type of tourist traffic. As a result of the proposed measures one can expect increase of passenger traffic on the railroad, image improvement of the Ukrainian railways within the country and abroad, attraction of additional funds to renew the outdated infrastructure and rolling stock, restoration of the objects of cultural and historical significance, creation of new jobs, and restraining of migration processes in western Ukraine.